Evolution of the main macroeconomic indicators as a result of Romania\’s integration into the EU - Ana-Maria URÎȚESCU (Theoretical and Applied Economics, 2018)

(untitled)
The purpose of this paper is to analyze the impact of the accession of our country to the EU based on the economy. The economic indicators analyzed are gross domestic product, budget deficit, government debt, government spending, government revenue, export and import. The analysis involves creating a multifactorial regression model with a dependent variable (gross domestic product) and as independent variables all other sets of data. Also, Granger\’s causality will be used to study the relationship between variables. The model results indicate a direct relationship between gross domestic product and the share of government budget deficits, the import on the gross domestic product, and an inversely relationship between gross domestic product and the shares of government debt, Government revenues and exports in the gross domestic product.